Simplification or technological development of processes for obtaining polymer materials - Olimova M. K; Obidov A (International Journal on Orange Technologies, 2021)
This article is devoted to the technology of polymer production and its continuous improvement in accordance with the state of the art. However, there are basic technological schemes for the production of polymers, and one should know the basic laws of the technological process for the production of various polymers. The main methods for producing polymers are polymerization, polycondensation, and chemical transformations of polymers